Evaluation of structural, dielectric, magnetic and photocatalytic properties of Nd and Cu co-doped barium hexaferrite. Issue 21 (1st November 2021) - Bibi, Firdous; Iqbal, Shahid; Sabeeh, Humera; Saleem, Tahira; Ahmad, Bashir; Nadeem, Muhammad; Shakir, Imran; Aadil, Muhammad; Kalsoom, Ambreen
Abstract: In this study, the micro-emulsion approach was adopted to fabricate rare earth (Nd) and transition metal (Cu) co-doped barium hexaferrite (Ba1-x Ndx Fe12-y Cuy O19 ) nanoparticles (NPs). The fabricated co-doped and undoped materials were characterized by FTIR, XRD, and SEM techniques for structural and morphological investigation. Structural studies such as XRD and FTIR confirmed Nd and Cu doping at the tetrahedral and octahedral sites of barium hexaferrite, respectively. The SEM analysis made sure that the materials were successfully produced at the nanoscale. Dielectric measurements revealed that the dielectric constant and AC conductivity values of the co-doped sample were higher than those of the undoped sample. The VSM study confirms the improved magnetic properties of the sample after co-doping that facilitates its separation and reuse after photocatalytic experiments. The co-doped and undoped sample's photocatalytic activities (PCA) were explored by comparing their Methyl Green (MG) dye degradation efficiencies. The results revealed that the co-doped barium hexaferrite sample degraded almost 92.6% of the MG dye, while the undoped sample degraded just 37.4%. The higher PCA of the co-doped sample is credited to its structural defects, which adjust the band interval to increase electrical conductivity. In addition, the co-doped sample lost only 2% photocatalytic efficiency after five successive cycles, demonstrating its potential for reuse. Application studies have clearly shown that our Nd-Cu co-doped barium hexaferrite sample has a great potential for practical application to remove toxic dyes from the environment. Graphical abstract: Image 1